Signal processing in random access. - Lang Tong (IEEE Signal processing magazine)
In this paper, a cross-layer view for roles of signal processing in random access network and vice versa is presented. The two cases where cross-layer design has a quantifiable impact on system performance are discussed. The first case is a small network (such as wireless LAN) where a few nodes with bursty arrivals communicate with an access point. The design objective is to achieve the highest throughput among users with variable rate and delay constraints. The impact of PHY layer design on MAC protocol is examined and illustrates a tradeoff between allocating resources to the PHY layer and to MAC layer. The second case, in contrast, deals with large-scale sensor networks where each node carries little information but is severely constrained by its computation and communication complexity and most importantly, battery power. This paper emphasizes that the design of signal processing algorithms must take into account the role of MAC and the nature of random arrivals and bursty transmissions.